Vegetation response to wildfire and climate forcing in a Rocky Mountain lodgepole pine forest over the past 2,500 years - Chileen, Barrie Victoria (Kansas State University, 2019)
Wildfire is a ubiquitous disturbance agent in Rocky Mountain subalpine forests. Lodgepole pine (Pinus contorta), a dominant tree species in subalpine forests of western North America, is largely resilient to high-severity fires. However, the resilience of lodgepole forests may be compromised with predicted changes to climate and moisture availability. While the modern post-fire dynamics of these systems are well studied, less is known about post-fire responses of lodgepole forests over the past few centuries and millennia. Thus, I investigated fire occurrence and post-fire vegetation change in a lodgepole forest over the past two millennia to understand ecosystem responses to variability in wildfire activity and climate. I reconstructed vegetation composition over the past 2,500 years in the small basin of Chickaree Lake, Colorado, U.S.A., in Rocky Mountain National Park. Pollen samples (n=52) were analyzed to characterize both broad-scale (centennial to millennial) trends in pollen assemblages associated with climate, and short-term (decadal) changes associated with multiple high-severity fire events previously reconstructed through charcoal analysis. Pollen assemblages were dominated by Pinus throughout the record. The primary broad-scale change in pollen composition characterized by an increase Artemisia and Rosaceae, and a decrease in mean Pinus and extra local pollen (Quercus, Salix, and Sarcobatus), which occurred around 1,155 calibrated years before present (cal yr BP). This change is coincident with a shift towards increased winter precipitation which characterizes modern climate identified from δO¹⁸ and lake level data. Wildfire occurrence resulted in significant decreases in Pinus pollen following the zone break at 1,155 cal yr BP, suggesting that impacts of fire on the composition of lodgepole pine forests may depend on underlying climate conditions. Throughout the past 2,500 years, vegetation composition returned to pre-fire conditions within 75 years, indicating overall resilience of Rocky Mountain lodgepole forests to fire activity despite some variability in post-fire vegetation recovery.
Keywords: Paleoecology; Wildfire; Rocky Mountain National Park; Pollen analysis; Climate change; Post-fire vegetation dynamics